Nutritional aspects of franchised fast food in Malaysia - Abdul Karim, Mohamad Nordin; Azudin, Mohd. Nasir (1988)
There is an increase in the number of franchised fast food outlets in Malaysia. They offer various foods ranging from fried chicken, burger, pizza, satay and murtabak. Satay and murtabak are Malaysia phenomenon and slowly joining the international market. Analysis on the nutritional content of these products were conducted. Parameters studied include protein, fat, carbohyrate, mineral, vitamin and calorific value. Protein contents of chicken based food items are 23±4 g%, burger 16±6 g%, pizza 18±8 g%, satay 41±1 g% and murtabak 7±1 g%. Calorific values of these products are 295±56 Kcal/100g (chicken based product), 260±19 Kcal/100g (burger), 251±47 Kcal/100g (pizza), 221±5 Kcal/100g (satay) and 189±23 Kcal/100g (murtabak). Preliminary studies on the popularity of franchised food outlets showed that chicken based products are the most popular choice of Malaysians.